2004
DOI: 10.1128/jcm.42.2.512-517.2004
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Differentiation of In Vitro-Spiked Bacteria by Real-Time PCR and Melting-Curve Analysis

Abstract: We introduce a consensus real-time PCR protocol for the detection of bacterial DNA from laboratoryprepared specimens such as water, urine, and plasma. This prototype detection system enables an exact Gram stain classification and, in particular, screening for specific species of 17 intensive care unit-relevant bacteria by means of fluorescence hybridization probes and melting-curve analysis in a one-run experiment. One strain of every species was tested at a final density of 10 6 CFU/ml. All bacteria examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 10 publications
0
34
0
Order By: Relevance
“…Moreover, there is a high risk of contamination by skin saprophytes such as coagulase-negative staphylococci (CoNS) and streptococci, which makes it difficult to implicate them as agents of catheterassociated bacteremia (9). All these issues can be overcome using PCR, because it is based on the direct detection of the microbe without relying on its growth curve or without suffering the bacteriostatic effect of antimicrobial therapy (12,20). In the present study, we evaluated a commercially available multiplex real-time PCR assay (the LightCycler SeptiFast test) for the direct detection of bacteria and fungi.…”
mentioning
confidence: 99%
“…Moreover, there is a high risk of contamination by skin saprophytes such as coagulase-negative staphylococci (CoNS) and streptococci, which makes it difficult to implicate them as agents of catheterassociated bacteremia (9). All these issues can be overcome using PCR, because it is based on the direct detection of the microbe without relying on its growth curve or without suffering the bacteriostatic effect of antimicrobial therapy (12,20). In the present study, we evaluated a commercially available multiplex real-time PCR assay (the LightCycler SeptiFast test) for the direct detection of bacteria and fungi.…”
mentioning
confidence: 99%
“…by Santos 5,20,21 . In the field of broad-range bacterial species identification, Klaschik et al 22 were the first to develop a PCR and melting analysis assay using 2 probes for identification of 17 common bacterial species. In 2006, Cheng et al 23 differentiated and identified 46 bacterial culture colonies representing 25 clinically important species using a LightCycler real-time PCR instrument for amplification of the 16S rRNA gene in the presence of the LC Green I fluorescent dye and a HR-1 melting instrument for melting profiles, without using any probe.…”
Section: Melting Analysis For Species Identification Purposesmentioning
confidence: 99%
“…Thus, it is necessary to develop a reliable broad-range detection system for bacterial DNA from clinical samples that is fast and easy to use and covers a wide range of clinically relevant microbes. Until now, broad-range real-time PCR assays have seldom been devised to identify bacterial DNA detected directly from clinical samples (18,23). Additionally, the simultaneous quantification and differentiation of a Gram stain with a broad-range real-time PCR in clinical blood samples is rarely described.…”
mentioning
confidence: 99%